Can different types of animation enchance recall and transer of knowledge? A case study on a computer science subject - Riaza Mohd Rias,; Halimah Badioze Zaman, (Penerbit Universiti Kebangsaan Malaysia, 2012)
Does animation play a role in learning? Compared to static visuals, multimedia animation is considered beneficial to learning, especially when the learning material demands visual movements. The emergence of three-dimensional animated visuals has expanded the presentation mode in multimedia learning. A case study on a computer science subject was used to test the effect of animation in learning. The field of computer science, especially in operating systems concepts, uses an array of abstract concepts such as virtual memory, paging, and fragmentations to describe and explain the underlying processes. Various studies, together with our own observations, strongly indicate that students often find these concepts difficult to learn because they cannot easily be demonstrated. This study investigates the effects of animation on student understanding when studying a complex domain in computer science, that is, the subject of memory management concepts in operating systems. A multimedia learning system was developed in three different versions: static graphics, 2-D animation, and 3-D animation. Fifty-five students participated in this study and were randomly assigned to one of the three groups. All participants had little prior knowledge in this subject. After viewing a lesson, they were asked to take a test that assessed their recall and transfer of knowledge. This test was used to determine if, in fact, improved learning occurred and the version of animation that produced the better outcome. An initial analysis of the results showed no statistical difference between the scores for the three versions, which suggests that animations, by themselves, do not necessarily improve student understanding.